E-Governance in India-Best Practice: An Overview of Kerala State - Sefiya K.M (POST GRADUATE DEPARTMENT OF COMMERCE AND MANAGEMENT STUDIES SRI C ACHUTHA MENON GOVERNMENT COLLEGE, THRISSUR, KERALA, 2013)
E-governance or electronic governance refers to the application of Information and Communication Technologies by government agencies for exchange of information, communication, transaction with citizens, businesses or other government departments. It aims at providing public services effectively, efficiently and equitably to the citizens. Good governance is a competent management of a country’s resources and affairs in a manner which is transparent, open, accountable, equitable and responsive to people’s needs. The Government has launched several programmes for attaining the strategy inclusive growth. These initiatives have brought in some transparency through its advertisements. It becomes more beneficial to its beneficiaries and also raising public consciousness and confidence among public. The system should be transparent through good governance.